Efficacy of Enteral Nutrition by Double Elementary Diet Tube after Pylorus-Preserving Pancreatoduodenectomy. Issue 4 (April 2019) - Sano, Toru; Chiba, Naokazu; Gunji, Takahiro; Ozawa, Yosuke; Hikita, Kosuke; Okihara, Masaaki; Tomita, Koichi; Oshima, Go; Takano, Kiminori; Abe, Yuta; Shimazu, Motohide; Kawachi, Shigeyuki
Nutritional support after pylorus-preserving pancreaticoduodenectomy (PpPD) is still controversial. This study aimed to evaluate the efficacy of enteral nutrition (EN) via the double elementary diet (W-ED) tube after PpPD. One hundred two patients who received EN by the W-ED tube were compared with 52 patients who received total parental nutrition (TPN) previously. Clinicopatho-logical and postoperative features were analyzed among the two groups. Patients with EN by the W-ED tube after PpPD had a lower incidence of postoperative pancreatic fistula than those with TPN. The total protein and albumin levels on discharge in the EN group were significantly higher than those in the TPN group. In the case without complication, decreasing rate of the third lumbar vertebra skeletal muscle area was significantly lower in the EN group. In the cases of soft pancreas, drainage volume by the W-ED tube until four postoperative day was significantly larger in the case without postoperative pancreatic fistula. The W-ED tube offers the advantages of reducing gastrointestinal pressure and enabling reduction of complications after PpPD surgery.